A durable and high-flux composite coating nylon membrane for oil-water separation. (20th August 2018) - Zhang, Xinying; Wang, Chaoqun; Liu, Xiaoyan; Wang, Jinhua; Zhang, Chenying; Wen, Yuling
Abstract: A durable and high-flux superhydrophilic-underwater superoleophobic oil-water separation membrane was prepared for effective oil-water separation by cellulose-starch-silica surface charging and hydrophilization. The surface properties of the composite coating nylon membrane were characterized by contact angle and scanning electron microscopy. The chemical structures of this membrane were confirmed by Fourier transform infrared spectroscopy and energy dispersive X-ray spectrometer. This membrane showed excellent hydrophilicity and underwater oleophobicity. After modified, the water contact angle of the membrane attained 0̊, and the underwater oil contact angles reached 159.5̊̊. The cellulose-starch-silica composite coating nylon membrane exhibited high oil-water separation efficiency (99.8%) for hexane, and it was also efficient for cyclohexane, petroleum ether, diesel, soybean oil, lubricating oil and silicone oil. Besides, the membrane flux could reach 31847 L −1 m −2  h −1  bar −1 . It showed this membrane had a high efficiency for oil-water separation. The modified nylon membrane was durable for oil-water separation. The separation efficiency could still retained above 97% after 100 cycles, and the modified nylon membrane still worked well after 24 h in harsh environment (pH value 4 to 10). The whole separation process could be achieved successfully without depending on any extra power. This work provided a new strategy to fabricate superhydrophilic and underwater superoleophobic membrane with good reusability, high flux and stability for oil-water separation. Graphical abstract: Image Highlights: This study provideda new strategy to fabricate underwater superoleophobic membrane. The obtained membranes was green and environmentally friendly. The obtained membranes had excellent durability and high-flux.